2020
DOI: 10.1021/acsami.0c09739
|View full text |Cite
|
Sign up to set email alerts
|

Minimalization of Metallic Pd Formation in Suzuki Reaction with a Solid-State Organometallic Catalyst

Abstract: Suzuki reaction usually uses palladium (Pd) complexes to accommodate a wide range of substrates. In pursuing greener synthesis, immobilization of Pd complexes with various support materials has shown promising potential. Although this approach can give stable conversion, initially immobilized Pd ions are largely reduced to Pd 0 aggregates and turned essentially into supported nanoparticles after use, which departs from its original intention of complex immobilization and thus hampers its activity. Herein, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 64 publications
4
37
0
Order By: Relevance
“…The pristine pre-catalyst Pd/PECIm displays two signals centered at 337.9 eV and 343.3 eV (Figure 3A), which agree with those observed for Pd(II). [27,50,55] This result confirms that, as expected, no reduction takes place during the binding of the Pd ions to the polymer support. After the SM reaction, new signals appear at 335.2 eV and 340.4 eV (Figure 3B) which can be attributed to formation of Pd(0).…”
Section: Post-reaction Catalyst Characterizationsupporting
confidence: 88%
See 3 more Smart Citations
“…The pristine pre-catalyst Pd/PECIm displays two signals centered at 337.9 eV and 343.3 eV (Figure 3A), which agree with those observed for Pd(II). [27,50,55] This result confirms that, as expected, no reduction takes place during the binding of the Pd ions to the polymer support. After the SM reaction, new signals appear at 335.2 eV and 340.4 eV (Figure 3B) which can be attributed to formation of Pd(0).…”
Section: Post-reaction Catalyst Characterizationsupporting
confidence: 88%
“…Our results are in agreement with the current view that chemical reduction of Pd(II) into Pd(0) on the surface of the precatalyst diminishes its performance. [27] In fact, when fresh Pd/ PECIm was reduced with NaBH 4 it becomes inactive (results not shown), indicating that keeping a large Pd(II)/Pd(0) ratio is of paramount importance for catalyst performance. In line with our findings, Li and Zeng [27] reported that minimization of metallic palladium formation and aggregation is important to maintain catalyst activity in the Suzuky-Miyaura cross-coupling.…”
Section: Chemcatchemmentioning
confidence: 96%
See 2 more Smart Citations
“…Along a similar line, in a very recent work by our group, spherical organosilica was prepared solely from 3-mercaptopropyl trimethoxysilane (MPTMS) and demonstrated to be an effective Pd(II) reservoir for Suzuki coupling reactions with decent recyclability and minimum metallic Pd formation. 18 However, presumably due to the strong binding between thiolate ligands and Pd(II) species, only a thickness of 40 nm from the surface could be effectively utilized for immobilization of Pd ions, while Au ions could be more evenly distributed across the entire sphere. 18 This largely limits the utilization of the support material, yet still inhibiting the Pd-ion shuttling and release, as Pd ions have to travel across a distance of 40 nm inside the organosilica matrix before reaching the reacting liquid phase.…”
Section: Introductionmentioning
confidence: 99%